Accuracy of Nutritional Screening Tools in Assessing the Risk of Undernutrition in Hospitalized Children. Issue 2 (August 2015) - Huysentruyt, Koen; Devreker, Thierry; Dejonckheere, Joachim; De Schepper, Jean; Vandenplas, Yvan; Cools, Filip
Abstract Objective: The aim of the present study was to evaluate the predictive accuracy of screening tools for assessing nutritional risk in hospitalized children in developed countries. Methods: The study involved a systematic review of literature (MEDLINE, EMBASE, and Cochrane Central databases up to January 17, 2014) of studies on the diagnostic performance of pediatric nutritional screening tools. Methodological quality was assessed using a modified QUADAS tool. Sensitivity and specificity were calculated for each screening tool per validation method. A meta-analysis was performed to estimate the risk ratio of different screening result categories of being truly at nutritional risk. Results: A total of 11 studies were included on ≥1 of the following screening tools: Pediatric Nutritional Risk Score, Screening Tool for the Assessment of Malnutrition in Paediatrics, Paediatric Yorkhill Malnutrition Score, and Screening Tool for Risk on Nutritional Status and Growth. Because of variation in reference standards, a direct comparison of the predictive accuracy of the screening tools was not possible. A meta-analysis was performed on 1629 children from 7 different studies. The risk ratio of being truly at nutritional risk was 0.349 (95% confidence interval [CI] 0.16–0.78) for children in the low versus moderate screening category and 0.292 (95% CI 0.19–0.44) in the moderate versus high screening category. Conclusions: There is insufficient evidence to choose 1 nutritional screening tool over another based on their predictive accuracy. The estimated risk of being at "true nutritional risk" increases with each category of screening test result. Each screening category should be linked to a specific course of action, although further research is needed.